Chest CT tomography vs. intracavitary electrocardiogram guidance in predicting the length of PICC placement - Huimin Dong; Yuxin Zhu; Xin Zhang; Xinxin Yin; Fude Liu (BMC Surgery, 2022)
Abstract Background To evaluate chest computed tomography (CT) compared to intracavitary electrocardiogram (ECG) in predicting the length of peripherally inserted central catheter (PICC) placement and analyzing the accuracy of the positioning methods. Methods This study included a total number of 436 patients who underwent PICC placement. The patients enrolled were randomly divided into two groups: ECG group (n = 218, received IC-ECG) and chest CT group (n = 218, received chest CT). The tip length of the catheter in the superior vena cava, the measured length of the catheter and the actual insertion length of the catheter were observed and recorded in the two groups. Results The best catheterization rate of tip positioning and the one-time placement rate of tip positioning in ECG group were significantly higher than that in the chest CT group (all P < 0.05). The comfort level and satisfaction rate in ECG group was significantly higher than that of chest CT group (all P < 0.05). Conclusion Accurate catheterization length could be achieved by both chest CT and intracavitary electrocardiogram guidance in the process of predicting PICC placement length. However, IC-ECG guided procedure was more worthy of promotion in clinic.